Incidence, predictors and prognostic impact of intracranial bleeding within the first year after an acute coronary syndrome in patients treated with percutaneous coronary intervention. Issue 7 (1st October 2020) - Raposeiras-Roubín, Sergio; Abu-Assi, Emad; Caneiro Queija, Berenice; Cobas Paz, Rafael; D'Ascenzo, Fabrizio; Henriques, Jose Paulo Simao; Saucedo, Jorge; González-Juanatey, José; Wilton, Stephen B; Kikkert, Wouter J; Nuñez-Gil, Iván; Ariza-Sole, Albert; et al.
Abstract : Background: The rate of intracranial haemorrhage after an acute coronary syndrome has been studied in detail in the era of thrombolysis; however, in the contemporary era of percutaneous coronary intervention, most of the data have been derived from clinical trials. With this background, we aim to analyse the incidence, timing, predictors and prognostic impact of post-discharge intracranial haemorrhage in patients with acute coronary syndrome undergoing percutaneous coronary intervention. Methods: We analysed data from the BleeMACS registry (patients discharged for acute coronary syndrome and undergoing percutaneous coronary intervention from Europe, Asia and America, 2003–2014). Analyses were conducted using a competing risk framework. Uni and multivariate predictors of intracranial haemorrhage were assessed using the Fine–Gray proportional hazards regression analysis. The endpoint was 1-year post-discharge intracranial haemorrhage. Results: Of 11, 136 patients, 30 presented with intracranial haemorrhage during the first year (0.27%). The median time to intracranial haemorrhage was 150 days (interquartile range 55.7–319.5). The fatality rate of intracranial haemorrhage was very high (30%). After multivariate analysis, only age (subhazard ratio 1.05, 95% confidence interval 1.01–1.07) and prior stroke/transient ischaemic attack (hazard ratio 3.29, 95% confidence interval 1.36–8.00) were independently associated with a higher risk of intracranial haemorrhage. Hypertension showed a trend to associate with higher intracranial haemorrhage rate. The combination of older age (⩾75 years), prior stroke/transient ischaemic attack, and/or hypertension allowed us to identify most of the patients with intracranial haemorrhage (86.7%). The annual rate of intracranial haemorrhage was 0.1% in patients with no risk factors, 0.2% in those with one factor, 0.6% in those with two factors and 1.3% in those with three factors. Conclusion: The incidence of intracranial haemorrhage in the first year after an acute coronary syndrome treated with percutaneous coronary intervention is low. Advanced age, previous stroke/transient ischaemic attack, and hypertension are the main predictors of increased intracranial haemorrhage risk.